Penguatan Literasi Desain Grafis Digital pada Siswa SMP melalui Pelatihan Berbasis Figma - Deven Christian Aditya; Adela Desca Angelica Putri; Gabriela Mitchelle Hendri; Darren Santiago Charlie; Charlisya Greely; Paulus Mudjihartono (Jurnal Atma Inovasia, 2026)
The graphic design workshop using Figma for students of SMP Stella Duce 1 Yogyakarta was conducted to enhance students’ digital literacy, creativity, and critical thinking skills in producing digital design works. This program was initiated due to students’ limited ability in digital design and the limited use of digital learning media at school. The workshop aimed to provide students with an understanding of basic graphic design principles and technical skills in using Figma as a collaborative design platform. The method included needs analysis, module development, and hands-on training in the computer laboratory through material presentation, mini-challenges, and guided practice in creating digital posters. The results showed that students were able to follow the training flow and successfully produced simple digital poster designs. Evaluation using online questionnaires completed by 17 participants indicated positive responses, with 14 participants (82.4%) stating that the workshop was beneficial and 15 participants (88.2%) affirming that the activity aligned with the school’s needs. The program is concluded to be effective in strengthening students’ digital literacy and design skills, although longer sessions are recommended to optimize practice and project completion.